Microstructure evolution and strengthening mechanism of Al0.4CoCu0.6NiSix (x=0–0.2) high entropy alloys prepared by vacuum arc melting and copper injection fast solidification. (April 2018) - Chen, Yongxing; Zhu, Sheng; Wang, Xiaoming; Yang, Baijun; Han, Guofeng; Qiu, Liu
Abstract: The work prepared Al0.4 CoCu0.6 NiSix (x = 0, 0.05, 0.1, 0.2) high entropy alloys by vacuum arc melting (Mx ) and copper injection fast solidification (Ix ), discussed the influence of trace Si and rapid cooling on the alloys' microstructures and mechanical properties, analyzed the alloys' strengthening mechanism and evaluated the proportion of different strengthening effects on the improved mechanical properties. The results showed that Mx had a fcc + L12 structure, but it transformed to fcc + L12 + minor bcc when x = 0.1 and 0.2. Ix had a fcc + L12 structure except I0.2 (fcc + L12 + minor bcc). With the increase of silicon, Mx 's hardness increased from 193 HV to 334 HV and Ix 's hardness increased from 216 HV to 395 HV. M0.2 's yield strength increased to 588 MPa, which was 2 times than that of M0, the fracture strength and plastic deformation were 3074 MPa, 40.5%. Ix 's yield strength increased to 690 MPa, which was 2.3 times than that of M0, the fracture strength and plastic deformation reached 3407 MPa, 33.1%. The alloys' strengthening mechanism was the formation of bcc phase, solid solution strengthening and fine grain strengthening. And the strengthening effect of bcc phase was greater than fine grain strengthening and the fine grain strengthening effect was greater than solid solution strengthening. Highlights: Arc melted and copper injected Al0.4 CoCu0.6 NiSix(x=0-0.2) HEAs were prepared. Effects of Si micro-alloying and rapid cooling on HEAs were analyzed. New phase, solid solution, fine grain strengthening mechanisms were introduced. Build a solid solution model and evaluate the three strengthening patterns. Realize the combination of HEAs' high strength and excellent plasticity.